Quarterly labour force statistics / OECD, Department of Economics and Statistics = Statistiques trimestrielles de la population active / Département des affaires économiques et statistiques, OCDE - Organisation for Economic Co-operation and Development. Dept. of Economics and Statistics.
Labour force statistics (Paris, France). Quarterly supplement to the yearbook, ISSN 0304-3312.